TORTURE AND OTHER CRUEL, INHUMAN OR DEGRADING TREATMENT OR PUNISHMENT IN GEORGIA PRISONS AS PART OF CRIMINAL JUSTICE POLICY - Beselia, Eka (European Scientific Journal, ESJ, 2013)
For nearly a decade, a significant amount of research, investigations, and scandals in mass media has produced a new understanding about the threat of violence in penitentiaries and the changing the international approaches to this phenomenon. Experience has shown that almost no country is immune from practices that amount to torture and ill-treatment. In the article author explores the reasons and scope of torture in the law enforcement and penitentiary systems of Georgia. Particularly author analyzed: reasons for the torture of the accused offenders on the stage of preliminary investigation; violence as a result of overcrowding in closed correctional facilities public policy and investigation of torture; and reasons for the use of force in prisons.